Effects of guanidine derivatives on mitochondrial function: I. Phenethylbiguanide inhibition of respiration in mitochondria from guinea pig and rat tissues - Davidoff, Frank (1968)
Derivatives of guanidine, such as phenethylbiguanide, are potent inhibitors of mitochondrial respiration in vitro, but the relevance of this inhibition to their in vivo blood sugar-lowering action is not clear. We have studied the metabolism of pyruvate and long chain fatty acids by mitochondria from several tissues of guinea pigs and rats and observed the effects of phenethylbiguanide on these processes. The rate of pyruvate decarboxylation and of β-oxidation of long chain fatty acyl-CoA derivatives by guinea pig heart mitochondria in vitro has been found to exceed the flux of substrate through the citric acid cycle, both in the presence and absence of phosphate acceptor. When serum albumin is included in the incubation medium, the respiration of guinea pig heart, skeletal muscle, and liver mitochondria is inhibited by concentrations of phenethylbiguanide which approximate the levels achieved in those tissues in vivo. In the absence of albumin, the mitochondria are several fold less sensitive to phenethylbiguanide inhibition. Mitochondria from rat tissues are less sensitive than those of guinea pig to in vitro inhibition by phenethylbiguanide, but serum albumin alters sensitivity to inhibition in similar fashion in both species. During the breakdown of pyruvate or long chain fatty acyl-CoA, phenethylbiguanide demonstrates no specificity of inhibition toward the oxidative reactions before the citric acid cycle versus those of the cycle itself. However, oxidation of free fatty acids is relatively resistant to inhibition.